قناع الحسين ’معرفية التعايش و روح التكامل الإنساني في نصوص أمل دنقل ، أدونيس ، البياتي - عزوز, لحسن (University of eloued جامعة الوادي, 2016)
Humanity, are the intersections of view philosophical and ethical depends on the value and efficiency of the human in a constant dialogisme talk shows, whether an individual or a group, and interfere in general thinking and reasoning, not imagined a human could revolutionize played in ancient years revolution amazing, at an undisclosed location in the world and in the day of history .. To turn into a song of tongues spoken by poets through the ages and ages .. It was not able revolution in the long human history of Imam Hussein, a revolution that erupted literary and poetic revolution and create a giant curricula and studies of poetry in Arabic literature, and to perpetuate the poets to this day we still hail Baksaidhm and poetry
ملتقى الطف العلمي و الثقافي الدولي الثامن - الجامعة المستنصرية كلية الآداب - العراق
Keywords: القناع ، تعددية ثقافية ، المواطنة ، حضارة ، حوارية; MASQUE ، Persona ، Shadow, multiculturalisme, Citoyenneté, civilisation, dialogisme